Lacan a zoontology (or how my dog and I figure in the Anthropocene) - Dela Cruz, Aaron Philip M. (Dunong: UP Diliman Journal of Student Research, 2021)
Access online through this link: https://journals.upd.edu.ph/index.php/Dunong/article/view/8865/7924